Saberes docentes na universidade: estudo de casos múltiplos em Cursos de Ciências Contábeis do Sudoeste do Paraná - Wronski, Pollyanna Gracy (2023)
Teacher training is a widely discussed topic in the area of Education due to its importance and overlaps, including in Higher Education. There is a growing concern about teaching in undergraduate courses, so it is essential that professionals who work in initial training present the necessary knowledge for their work. In this context, it is highlighted that the literature points out that the teacher must present a set of knowledge, from different origins that must be stimulated and built throughout their practice. One of the authors who classifies this knowledge is Tardif (2002), who categorizes them as professional, disciplinary, curricular and experiential knowledge, which are specific knowledge that relate to the teaching professional experience. The multiple case study of this dissertation presents a bibliographical, documental and field research carried out with professors of the Accounting Sciences course who work in two private institutions in the southwest of Paraná. The research aimed to analyze to what extent the knowledge of the Accounting Sciences course professors at Higher Education Institutions in the southwest of Paraná helps in their professional activity. The analytical approach was quali/quantitative. Data were captured through the application of questionnaires and interviews and indicated that all types of knowledge are a concern of teachers and are related to their pedagogical practice. Experiential knowledge was indicated as one of the most important and pedagogical and disciplinary knowledge as those that deserve greater attention. Teachers pointed out weaknesses in their pedagogical training and highlighted the need for continuing education for better qualification and professional performance.